Plasma‐assisted fabrication of multiscale materials for electrochemical energy conversion and storage - Chen Li; Tengfei Zhang; Zhong Qiu; Beirong Ye; Xinqi Liang; Xin Liu; Minghua Chen; Xinhui Xia; Chen Wang; Wangjun Wan; Yongqi Zhang (Carbon Energy, 2025)
Abstract Plasma, the fourth state of matter, is characterized by the presence of charged particles, including ions and electrons. It has been shown to induce unique physical and chemical reactions. Recently, there have been increased applications of plasma technology in the field of multiscale functional materials' preparation, with a number of interesting results. This review will begin by introducing the basic knowledge of plasma, including the definition, typical parameters, and classification of plasma setups. Following this, we will provide a comprehensive review and summary of the applications (phase conversion, doping, deposition, etching, exfoliation, and surface treatment) of plasma in common energy conversion and storage systems, such as electrocatalytic conversion of small molecules, batteries, fuel cells, and supercapacitors. This article summarizes the structure–performance relationships of electrochemical energy conversion and storage materials (ECSMs) that have been prepared or modified by plasma. It also provides an overview of the challenges and perspectives of plasma technology, which could lead to a new approach for designing and modifying electrode materials in ECSMs.